The impact of the first wave of the COVID-19 pandemic on hospital admissions and treatment management of ectopic pregnancy - Hande Gurbuz; Gulfem Basol; Mehmet Mustafa Altintas; Betul Kuru (Turkish Journal of Emergency Medicine)
OBJECTIVES: We aimed to evaluate the clinical features and treatment strategies applied to the patients with ectopic pregnancy admitted to our tertiary care center before and during the pandemic. METHODS: Women aged 18–45 years, who were admitted to the hospital with a diagnosis of ectopic pregnancy in the pre- and postpandemic periods, were included in this case–control study. RESULTS: A total of 173 patients, 116 patients before the pandemic and 57 patients during the pandemic, were included in the study. The rate of admissions from the emergency department was higher during the pandemic than before the pandemic (P = 0.003). The rupture was detected significantly higher during the outbreak (13/116 [11.2%]) than before the pandemic (16/57 [28.1%]) (P = 0.009). While conservative treatment was applied more frequently in the prepandemic period, it was observed that patients were treated surgically more frequently during the pandemic period (P = 0.003). While laparoscopic surgery was preferred before the pandemic, laparotomy was applied to all patients during the pandemic (P < 0.001). CONCLUSIONS: In the first wave of the outbreak, there were delays in the diagnosis of ectopic pregnancies, and these patients presented with ruptures more frequently than before the pandemic. Furthermore, surgical treatment methods were used more than conservative therapies during the outbreak.